SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI; METODE PROFILE MATCHING - Zulfahmi Fahmi; Faradika Dika (Prodi Sistem Informasi Universitas Dharma Andalas, 2019)
This research was conducted to assist the school in terms of selection of creative students, especially those using Kurikulum 2013 or better known as K-13. We conclude that the subjective application of student achievement with the 2006 curriculum is more commonly referred to as Kurikulum Tingkat Satuan Pendidikan (KTSP) has been widely circulated schools. The limits given in the decision support system of selecting student achievement include the determination of criteria and using Profile Matching method which leads to the determination of GAP value, the smaller the gap value the greater the chance to be selected as a student achievement. In designing applications researchers use using tools such as UML ( Unified Modeling Language) in order to make it easier to move the concept of a system designed into the form of the program.